Elements of the niche for adult stem cell expansion. (22nd August 2017) - Redondo, Patricia A; Pavlou, Marina; Loizidou, Marilena; Cheema, Umber
Adult stem cells are crucial for tissue homeostasis. These cells reside within exclusive locations in tissues, termed niches, which protect adult stem cell fidelity and regulate their many functions through biophysical-, biochemical- and cellular-mediated mechanisms. There is a growing understanding of how these mechanisms and their components contribute towards maintaining stem cell quiescence, self-renewal, expansion and differentiation patterns. In vitro expansion of adult stem cells is a powerful tool for understanding stem cell biology, and for tissue engineering and regenerative medicine applications. However, it is technically challenging, since adult stem cell removal from their native microenvironment has negative repercussions on their sustainability. In this review, we overview specific elements of the biomimetic niche and how recreating such elements can help in vitro propagation of adult stem cells.